Щенок Элли, или Долгая дорога домой - Вебб Холли (Добрые истории о зверятах, 2017)
Экземпляры: ф.16 (20210409) / Инвентарный номер: 60743 / Цена: / Сис.шифр: 84(4Вел)-4 / Авт.знак: В 26 / ГРНТИ: 17.82.93 / ББК: 84(4Вел)-44